FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MEMILIH JURUSAN AKUNTANSI (Studi Empiris Pada Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Shela Susanti; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2022)
This research objective is to know the factors that influence students' interest in choosing a lecture in the accounting department. This study used primary data with the following criteria: active students majoring in accounting, Faculty of Economics and Business, Islamic University of Malang, class 2018-2021. The collection method is through a questionnaire via google form using a Likert scale of 1-5. 120 students were used as the research sample, data analysis methods with multiple linear regression analysis. The study results prove that Interests, Peers, Cost of Education, Accreditation of Study Programs, and Job Opportunities significantly affect student decisions in choosing major accounting majors. Keywords: interest, peers, tuition fees, study program accreditation, job opportunities, decision to choose Accounting Department. Keywords: interests, peers, education costs, study program accreditation, job opportunities and decisions.